Characterisation and evaluation of a PNP strip detector for synchrotron microbeam radiation therapy. (21st June 2018) - Davis, Jeremy A; Paino, Jason R; Dipuglia, Andrew; Cameron, Matthew; Siegele, Rainer; Pastuovic, Zeljko; Petasecca, Marco; Perevertaylo, Vladimir L; Rosenfeld, Anatoly B; Lerch, Michael L F
Abstract: The Quality Assurance requirements of detectors for Synchrotron Micro-beam Radiation Therapy are such that there are limited commercial systems available. The high intensity and spatial fractionation of synchrotron microbeams requires detectors be radiation hard and capable of measuring high dose gradients with high spatial resolution sensitivity. Silicon single strip detectors are a promising candidate for such applications. The PNP strip detector is an alternative design of an already proven technology and is assessed on its contextual viability. In this study, the electrical and charge collection efficiency properties of the device are characterised. In addition, a dedicated TCAD model is used to support ion beam induced charge measurements to determine the spatial resolution of the detector. Lastly, the detector was used to measure the full width half maximum and peak to valley dose ratio for microbeams with only a slight over response. With the exception of radiation hardness the PNP detector is a promising candidate for quality assurance in microbeam radiation therapy.